Optimal energy saving control of mine coal transportation system based on machine visio - GUO Weidong; LI Ming; KANG Junming; LEI Meng; ZHU Meiqiang (Gong-kuang zidonghua, 2020)
In order to optimize control of energy saving, the key to coal transportation system is real-time detection of coal flow of belt conveyor and frequency conversion speed regulation control according to coal flow. At present, most of mine belt conveyor adopts frequency conversion drive mode, but frequency converter does not adjust speed in stable operation stage, and keeps running under power frequency, so optimal energy saving of coal transportation system cannot be realized. Aiming at the above problem, an optimal energy saving control method of mine coal transportation system based on machine vision was proposed. Real-time coal flow image of belt conveyor is obtained by using laser emitter to assist digital camera, and noise interference of abnormal highlight spot in the image is removed through preprocessing. Direction template method is adopted to extract center line of laser stripe in the image and linear interpolation method is used to repair broken center line. Center line of belt laser baseline under no-load state and center line of coal flow laser profile under load state are superimposed to form a closed envelope curve, and instantaneous coal flow in the section enclosed by the curve is calculated. PLC fuzzy controller controls inverter output frequency according to expected belt speed calculated depending on coal flow and current belt speed collected by speed sensor, and then adjusts motor speed, so as to realize automatic adjustment of operating speed of belt conveyor according to coal flow. Information processing platform of ground control center is responsible for data collection, processing and display, and realizes visual monitoring and intelligent management of the mine coal transportation system. The method can quickly and effectively detect coal flow and adjust operating speed of belt conveyor in real time according to the coal flow, so as to achieve goal of energy saving, consumption reduction and economic operation of the mine coal transportation system.